Implementation of the Five Principles of Personality Through Programs and Activities of Students at Pondok Modern Darussalam Gontor - Rasyiddin, Achmad; Ridha, Arif; Fatimah, Fatimah (STIT Ahlussunnah Bukittinggi, 2022)
Having a person with good morals and being able to respond to various kinds of moral decline that hinder educational development. So its implementation is very necessary as a first step in building the moral education system of the Indonesian nation. The formulation in this research contains an explanation of the concept of cultivating the five souls in the formation of santri morals at Pondok Modern Darussalam Gontor, the application of the five souls in forming santri morals at Pondok Modern Darussalam Gontor, the application of the five souls in forming santri morals at Pondok Modern Darussalam Gontor, as well as factors supporting and inhibiting the five souls in the formation of morals. This type of research is a type of qualitative descriptive research. This research is field research, the methods used are observation, interviews and documentation. The data source for this research is the Pondok Modern Darussalam Gontor 9 family. Data analysis used in this research uses a data reduction method which is then presented in descriptive form and verified by drawing conclusions. The results of the research show that the concept of five soul education at Pondok Modern Darussalam Gontor 9.